1993
DOI: 10.1128/jb.175.3.785-794.1993
|View full text |Cite
|
Sign up to set email alerts
|

Nucleotide sequence of the Serratia marcescens threonine operon and analysis of the threonine operon mutations which alter feedback inhibition of both aspartokinase I and homoserine dehydrogenase I

Abstract: The nucleotide sequence of the Serratia narcescens threonine operon (thrA$,2BC) was determined. Three long open reading frames were identified; these open reading frames code for aspartokinase I (AKI)-homoserine dehydrogenase I (HDI), homoserine kinase, and threonine synthase, in that order. The predicted amino acid sequences of these enzymes were similar to the amino acid sequences of the corresponding enzymes in Escherichia coli. The AKI-HDI protein is apparently a tetramer composed of monomer polypeptides t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
28
0

Year Published

1993
1993
2008
2008

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 48 publications
0
28
0
Order By: Relevance
“…Some of these mutants have been shown to be genetically deregulated with respect to relevant 2 biosynthetic pathways. However, recent more detailed analysis has revealed that mutations responsible for deregulation, such as the mutations in thrA [4], dapA [5], lysC [6], and gnd [7], resulted in only partial desensitization of the enzymes, despite continual efforts of strain improvement. This made us realize again that NTG mutagenesis is not necessarily the best to achieve high desensitization of regulatory enzymes.…”
Section: Introductionmentioning
confidence: 99%
“…Some of these mutants have been shown to be genetically deregulated with respect to relevant 2 biosynthetic pathways. However, recent more detailed analysis has revealed that mutations responsible for deregulation, such as the mutations in thrA [4], dapA [5], lysC [6], and gnd [7], resulted in only partial desensitization of the enzymes, despite continual efforts of strain improvement. This made us realize again that NTG mutagenesis is not necessarily the best to achieve high desensitization of regulatory enzymes.…”
Section: Introductionmentioning
confidence: 99%
“…The corresponding gene has been isolated from a number of bacteria [6][7][8][9][10][11] and from Saccharomyces cerevisiae [12]. In plants, only partial purification of threonine synthase has been achieved [13 15].…”
Section: Introductionmentioning
confidence: 99%
“…The ACT domain has been found in enzymes that are regulated by amino acids or purines and is involved in regulation by these effectors (Chipman and Shaanan, 2001). In Figure 5, only aspartate kinases for which single mutations affecting enzymatic activity or regulation have been described (Arévalo-Rodríguez et al, 1999;Bareich and Wright, 2003;Farfán, 1997;Follettie et al, 1993;Hernando-Rico et al, 2001;Kalinowski et al, 1991;Kikuchi et al, 1999;Marco-Marin et al, 2003;Martín-Rendón et al, 1993;Ogawa-Miyata et al, 2001;Ohnishi et al, 2002;Omori et al, 1993;Paris et al, 2003) are shown. Most but not all of those mutations affecting regulation are located in the ACT domains.…”
Section: Sequencing Of the Hom3-ts31d Hom3-r7 And Hom3-87wt Allelesmentioning
confidence: 99%
“…A few of them are in the amino acid kinase domain, viz. E282D and E279A in S. cerevisiae (this work; Bareich and Wright, 2003) (12) I522A (12) Q524 (12) AtAK-HD S301Y (8) G345D (8) AlAK E164K (6) K8R (5) E119D (5) R198K (5) D202E (5) E250K (7) G323D (7,6) M318I (6) L325F (6) T352I (7,6) V347M (6) T344M (7) S345L (7,6) EcAKIII S301Y (9) T311Y ( Bareich and Wright, 2003;(2) Arévalo-Rodríguez et al, 1999;(3) Martín-Rendón et al, 1993;(4) Farfán, 1997;(5) Marco-Marin et al, 2003;(6) Ogawa-Miyata et al, 2001;(7) Kikuchi et al, 1999;(8) Hernando-Rico et al, 2001;(9) Kalinowski et al, 1991;(10) Ohnishi et al, 2002;(11) Follettie et al, 1993;(12) Paris et al, 2003;(13) Omori et al, 1993Omori et al, et al, 1999Marco-Marin et al, 2003;O...…”
Section: Sequencing Of the Hom3-ts31d Hom3-r7 And Hom3-87wt Allelesmentioning
confidence: 99%